A case report of lung ultrasound missing a pneumothorax due to patient positioning. (November 2017) - Schrift, David; Barron, Keith; Wagner, Michael; Arya, Rohan
Lung ultrasound is increasingly utilized as a diagnostic tool for the detection of a pneumothorax. The effect of small changes in patient positioning on the accuracy of lung ultrasound to detect a pneumothorax is not well studied. We present the first known case of lung ultrasound missing a pneumothorax because of suboptimal patient positioning, and discuss the implications of our findings for clinicians that utilize lung ultrasound and for future research.